Experimental Test of Continuous Wave Frequency Diverse Array Doppler Radar - Nicholas R. Munson; Bill Correll; Ram M. Narayanan; Travis D. Bufler (Applied Sciences, 2025)
The frequency diverse array (FDA) is an antenna array architecture capable of beamforming in both range and angle. It improves upon the traditional phased array (PA), which can only achieve beamforming in angle. The FDA is configured to simultaneously scan in both range and angle using small frequency offsets across radiating elements, allowing beam scanning to occur from low-complexity RF hardware configurations. This work documents experimental data collections from four system evolutions of a prototype linear continuous wave (CW) FDA radar system, with emphasis on validating the system behavior at the signal model level. Data collected from these testing evolutions showcase the system as a potential low-complexity perimeter surveillance system with an auto-scanning mainbeam feature.